2010
DOI: 10.1074/jbc.m110.134262
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosines in the Carboxyl Terminus Regulate Syk Kinase Activity and Function

Abstract: The Syk tyrosine kinase family plays an essential role in immunoreceptor tyrosine-based activation motif (ITAM) signaling. The binding of Syk to tyrosine-phosphorylated ITAM subunits of immunoreceptors, such as Fc⑀RI on mast cells, results in a conformational change, with an increase of enzymatic activity of Syk. This conformational change exposes the COOH-terminal tail of Syk, which has three conserved Tyr residues (Tyr-623, Tyr-624, and Tyr-625 of rat Syk). To understand the role of these residues in signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 62 publications
2
42
0
1
Order By: Relevance
“…b). Tyrosine phosphorylation is required to activate Syk kinase activity and function . Thus, we examined Syk activity in SW480/ANGPTL2‐1 and ‐2 versus control cells by Western blotting with a phospho‐Syk antibody.…”
Section: Resultsmentioning
confidence: 99%
“…b). Tyrosine phosphorylation is required to activate Syk kinase activity and function . Thus, we examined Syk activity in SW480/ANGPTL2‐1 and ‐2 versus control cells by Western blotting with a phospho‐Syk antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are warranted to better understand the differential regulation of activation loop tyrosines in ITK-SYK. According to a recent report, loss of the C-terminal tyrosines in SYK led to enhanced phosphorylation in the activation loop tyrosines (30). In contrast, ITK-SYK was equally phosphorylated at the corresponding activation loop tyrosines 385/386 in the absence or presence of functional C-terminal tyrosines (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Phenylalanine replacement of tail tyrosines has been reported to result in gain-of-function in SYK family kinases (19). Another recent study showed that loss of C-terminal/tail tyrosines results in enhanced phosphorylation of SYK activation loop tyrosines 525/526, whereas downstream signaling events, such as nuclear factor of activated T cells and NFB activation, were severely hampered (30).…”
Section: The Inducible T Cell Kinase-spleen Tyrosine Kinase (Itk-syk)mentioning
confidence: 99%
“…This shows that in addition to the main regulatory Tyrosines Y348 and Y352, there are other residues that can be transphosphorylated by the Syk itself and that activate the kinase. While it has been shown that activation loop tyrosines Y525 and Y526 have little effect on Syk activity, it is well established that the C-terminal tyrosines Y630 and Y631 can stabilize the closed, inactive conformation of the enzyme (12,35), and thus phosphorylation of these could induce the activity of even the Y438F/Y352F mutant. In mouse, Syk residues corresponding to Y630 and Y631 have been found to be autophosphorylated or transphosphorylated (36).…”
Section: Discussionmentioning
confidence: 99%